Siyasah Al-Manahij Al-Wathaniyah: 1968 wa 1975 fi Ta'lim Al-Lughah Al-'Arabiyah - Rosyida, Salma; Makruf, Imam; Qosim, Muhammad Nanang (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
In the mid-20th century, Indonesia underwent significant changes in politics, economy, and society, which greatly impacted the national education system. During the New Order era, education was considered a strategic tool for achieving national goals, including economic development and political stability. This study aims to consider the implementation and effectiveness of the 1968 and 1975 curricula in Arabic language learning in Indonesia. The 1968 curriculum was enacted as part of the post-G30S/PKI national policy, with an emphasis on strengthening the Pancasila ideology and basic mastery of Arabic. Five years later, the 1975 curriculum was enacted with a more flexible and student-based approach, adapting education to the development of science as well as social and economic needs. This research uses a qualitative approach with library research methods. Data were collected by documenting educational policies, official curriculum documents, and related academic studies. The results showed that the 1968 curriculum was more structural by emphasizing the mastery of grammar and vocabulary, while the 1975 curriculum was more interactive by incorporating cultural and religious aspects in Arabic language teaching. However, both curricula are faced with challenges in their implementation, such as limited resources and the readiness of teaching staff. Thus, this study provides insights into the development of Arabic language education policy in Indonesia and its implications for future curriculum development.